Surface modelling by computer proceedings of a conference jointly sponsored by the Royal Institution of Chartered Surveyors and the Institution of Civil Engineers, and held in London on 6 October, 1976 - Darwent, Thelma J. (Institution of Civil Engineers, 1977)
These papers provide a review of surface modelling, present co-tidal charts and their uses, and focus on the engineering geology of south Essex.